ADAPTAÇÃO DE MÉTODO PROJETUAL NO PROJETO DE UM COCKPIT VEICULAR - Waltrick, Diego F.; Zanetti, Rafeel; Klein, Rodrigo; Tagliari, Rodrigo R.; Celuppi, Maria C.; Knop, Alice (Salão do Conhecimento, 2013)
Resumo